Concepts of religion in debates on secularization - Zielińska, Katarzyna (Approaching religion, 2013)
Defining the concept of religion is a recurring theme in the sociology of religion. Yet the constant attempts to determine the subject of the study do not necessarily indicate the immaturity of the discipline. The ongoing discussions are rather part of a broader problem, as the acceptance or rejection of certain understandings of the core concepts determines the scope of the discipline’s field. More importantly, it also permits other concepts to be understood, along with the social reality beyond them. Since the social reality is changing under the influence of various dynamics taking place in the contemporary globalised world, so should the conceptual apparatus aiming at describing those dynamics. This paper aims to grasp this changing nature of the central concept - that of religion. This is done through analysis of the debate on secularisation theories.